STUDY OF THYROID DISTURBANCE IN DIABETIC AND NON-DIABETIC CHRONIC KIDNEY DISEASE PATIENTS - El-Najjar, Mostafa; Emara, Mahmoud (JOURNAL OF ADVANCES IN BIOLOGY, 2016)
Objective: study the prevelance of thyroid disturbance in diabetic chronic kidney disease (CKD) patients and non-diabetic CKD patients. Background: CKD has been known to affect the pituitary-thyroid axis and the peripheral metabolism of thyroid hormones. Hyperthyroidism and hypothyroidism have been associated with insulin resistance which has been reported to be the major cause of impaired glucose metabolism in type 2 diabetes mellitus (T2DM). Methods: This study included (120) CKD patients aged from 25 years to 70 years from Menofia university hospitals during the period from May 2015 to October 2015. They were classified into two groups: (I) (64 patients) (Diabetic group), (II) (56 patients) (Non-diabetic group). Each group was subdivided into 2 subgroups (A,B) according to creatinine clearance (CrCl): (A) (CrCl>45ml/min), (B) (CrCl<45ml/min). Members of the study were subjected to thorough history taking, complete physical examination and to kidney function testing (serum creatinine (Scr), blood urea nitrogen (BUN)), hemoglobin A1c (HbA1c), thyroid function tests (TSH, free T3, free T4), thyroglobulin, serum albumin (SA). Results: The mean age in diabetic patients (group I) was 53.7 years while in non-diabetic patients (group II) was 46 years. The mean TSH for subgroup IA was 5.4 Î¼IU/ml while subgroup IB was 1.4 Î¼IU/ml and for subgroup IIA was 1.6 Î¼IU/ml while for subgroup IIB was 2.1 Î¼IU/ml. There was highly significant difference between subgroup IA and IB (p value=<0.001) and between subgroup IA and IIA (p value=<0.001). There was no significant difference between subgroup IIA and IIB (p value=0.658) and between subgroup IB and IIB (p value=0.467). Conclusion: This study shows that thyroid disturbance is more common in diabetic CKD patients than non-diabetic CKD patients and that hypothyroidism is more common in diabetic patients with early CKD stages than late CKD stages.